Bifid mandibular canal -an anesthetic challenge for maxillofacial surgeons- Case Report - Madan Nanjappa; Abhishek Bhattacharjee; Abhishek Khatua (Universidad de Concepción., 2018)
Bifid mandibular canal is a variation of the normal anatomy. Such anomalies can result in difficult anesthesia while performing surgeries of the posterior mandible under local anesthesia. Moreover there is a high chance of damaging the neurovascular bundle leading to complications. Here we present a case of a bifid mandibular canal which posed difficulty in achieving appropriate anesthesia. The inferior alveolar nerve is of special interest for maxillofacial and oral surgeons. Its relation with mandibular third molar plays an important role while performing disimpaction surgery, in cases of bilateral sagittal split osteotomy, prosthesis placement in resorbed ridges, mandibular trauma procedures, and may be traumatized by penetration of the implant drill.